The mediating role of treatment perceptions in the relationship between individual characteristics and engagement with a digital psychological intervention for pediatric chronic pain: a secondary data análisis - De la Vega, Rocío; Palermo, Tonya M. (My University, 2023)
This study tested the mediating role of treatment perceptions (difficulty and helpfulness) in the association between individual baseline characteristics (treatment expectancies and readiness to change) and treatment engagement (online and offline) with a digital psychological intervention for adolescents with chronic pain. A secondary data analysis of a single-arm trial of Web-based Management of Adolescent Pain, a self-guided internet intervention developed for the management of chronic pain in adolescents, was conducted. Survey data were collected at baseline (T1), midtreatment (ie, 4 weeks after the treatment started; T2), and post treatment (T3). In total, 85 adolescents with chronic pain participated. Several mediation models were significant in predicting online engagement. A significant indirect effect was found for the path expectancies–helpfulness–online engagement and for the path precontemplation–helpfulness–online engagement. Fourteen percent of the variance of online engagement was explained by the model including expectancies as a predictor, whereas 15% was explained by the model where readiness to change was the predictor. Offline engagement was partially explained in the model including readiness to change as the predictor but with marginal significance. Treatment perception, specifically, perceived helpfulness, was a mediator of the pathway between both treatment expectancies and readiness to change and online engagement with a digital psychological intervention for chronic pain. Assessing these variables at baseline and midtreatment may help to determine the risk of nonadherence. Further work is needed to confirm these mediation pathways in larger samples.
Keywords: Adolescentes - Psicología; Dolor - Aspectos psicológicos; Treatment adherence; Digital health; Psychological; Treatment; Treatment perceptions; Mediators; Pediatric pain; Psychological intervention; Self-management; Engagement; Intervention